A robust investment decision to deploy bioenergy carbon capture and storage—exploring the case of Stockholm Exergi - Stenström, Oscar; Khatiwada, Dilip; Levihn, Fabian; Usher, Will; Rydén, Magnus (Frontiers in Energy Research, 2024)
The upscaling of novel carbon dioxide removal, such as bioenergy carbon capture and storage (BECCS), to gigatonne scales is an urgent priority if global warming is to be limited to well below 2 °C. But political, economic, social, technological, environmental and regulatory uncertainty permeates BECCS projects and defers deters investors. To address this, we explore options to improve the robustness of BECCS deployment strategies in the face of multi-dimensional uncertainties. We apply Dynamic Adaptive Planning (DAP) through expert interviews and Robust Decision Making (RDM) through exploratory modelling, two decision-making under deep uncertainty methods, to the case of Stockholm Exergi, an early mover aiming to deploy BECCS at a combined heat and power plant in the capital of Sweden. The main contributions of the research are to (i) illustrate how a quantification of robustness against uncertainty can support an investment decision to deploy BECCS (ii) comprehensively cover uncertain vulnerabilities and opportunities of deploying BECCS, and (iii) identify critical scenarios and adaptations to manage these uncertainties. The main conclusions are: investing in BECCS is relatively robust against robustness criteria which rely on satisficingif assessing performance across many scenarios and which avoid worst-cases, while not investingif comparing the worst-cases of either investing, or not doing so. Not investing could miss out on up to € 3.8 billion in terms of net present value. The critical uncertainties of BECCS can be managed by strengthening biomass sustainability strategies and by gaining support for negative emission trading regulation on carbon markets, e.g. voluntary or Paris Agreement Article 6. Even in vulnerable scenarios of average electricity prices above 82 €/MWh, if trading regulation is implemented before 2030 and if negative emission prices exceed 151 €/CO2, investing in BECCS performs better than not doing so in 96 % of cases. We suggest that facility-level parameters and cost-reductions are of little importance for BECCS investments and upscaling. It is regulatory certainty of operating revenues, e.g. through negative emission markets, that needs to be provided by policymakers.